Halliday’s Social Semiotics in Practice: Exploring the Ideology of Kato Nan Ampek in Minangkabau Verbal Tradition - Fitri, Nidya; Intan, Angel Sophia; Widiasri, Dewa Ayu (Universitas PGRI Sumatera Barat, 2025)
This study investigates the speech system Kato Nan Ampek of the Minangkabau community through Halliday’s social semiotic framework. Kato Nan Ampek, comprising four speech forms—mandaki, manurun, mandata, and malereang—reflects Minangkabau values of politeness, hierarchy, and egalitarianism. The research aims to analyze how language structure (mood, modality, theme-rheme) constructs ideational, interpersonal, and textual meanings within traditional verbal communication. The study employs a qualitative descriptive method, collecting verbal texts from everyday Minangkabau interactions. Each utterance is examined using systemic functional linguistics (SFL), specifically analyzing the register components (field, tenor, and mode) and the three metafunctions. The findings reveal that each kato type corresponds to distinct social roles and communicative strategies. For example, Kato Mandaki is used when addressing elders, marked by indirect clause structures and low modality, signifying humility and respect. Kato Mandata, conversely, uses direct mood and informal particles to signify social equality and solidarity. Each speech act embeds cultural ideology and moral values mandaki enacts reverence for authority; manurun conveys affectionate instruction; mandata embodies communal harmony; and malereang expresses caution and politeness in formal interaction. These speech forms do not merely reflect cultural values but actively reproduce them through linguistic choices. The study affirms language as a semiotic resource that encodes ideology, social hierarchy, and identity. The paper contributes theoretically to local discourse studies by modeling how language is culturally shaped. Practically, it informs curriculum development, intergenerational language preservation, and revitalization strategies in the face of modernization. Future research should incorporate multimodal discourse (intonation, gesture), empirical dialogue data, and generational perceptions to deepen understanding of Kato Nan Ampek in a digital era.